Cucurbitacin B alleviates DSS-induced ulcerative colitis by improving gut microbiota disorder in C57BL/6 mice - Jichen Li; Xiaodi Shen; Xia Wu; Fan Zhao; Wenling Tang; Minglan Wu; Fang Hu; Xingjiang Hu; Fei Wang; Qiao Zhang (AMB Express)
Abstract Cucurbitacin B (CuB) is a triterpenoid compound derived from various medicinal plants, demonstrating potential anti-inflammatory, antioxidant, and neuroprotective properties, as well as significant anti-tumor effects. However, its efficacy in treating ulcerative colitis (UC) remains unclear. To investigate the therapeutic potential of CuB, a dextran sulfate sodium (DSS)-induced UC model in mice was employed, along with gut microbiota analysis. The results revealed that CuB significantly alleviated clinical symptoms, improved colonic tissue damage, and suppressed pro-inflammatory cytokines such as TNF-α, IL-1β, and IL-6 in colon tissues. Additionally, CuB was associated with changes in specific microbial populations, including the upregulation of Muribaculaceae, Rikenellaceae_RC9_gut_group, Muribaculum, and Bifidobacterium, and the downregulation of Desulfovibrionaceae, Helicobacter, Escherichia-Shigella, Streptococcus, Candidatus_Saccharimonas, and Clostridium, which may contribute to the recovery of colon injury. This study provides preliminary evidence supporting CuB's therapeutic potential in DSS-induced colitis by enhancing gut microbiota diversity. CuB shows promise as potential treatment for UC and other conditions related to disruptions in intestinal flora homeostasis.